2023
DOI: 10.1002/adfm.202301144
|View full text |Cite
|
Sign up to set email alerts
|

Polar Layered Bismuth‐Rich Oxyhalide Piezoelectrics Bi4O5X2 (XBr, I): Efficient Piezocatalytic Pure Water Splitting and Interlayer Anion‐Dependent Activity

Abstract: Piezocatalytic pure water splitting for H 2 evolution carries the virtues of efficacious utilization of mechanical energy, easy operation, and high value-added products, while lacking desirable piezoelectrics for high chemical energy production. Here, two polar layered bismuth-rich oxyhalides Bi 4 O 5 X 2 (XBr, I) thin nanosheets (≈4 nm) are first exploited as efficient piezocatalysts to be capable of dissociating pure water. The unique asymmetrical layered structures of Bi 4 O 5 X 2 (XBr, I) composed of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…In this case, the piezoelectric field will make electrons and holes transfer in opposite directions, thereby effectively inhibiting their recombination and allowing more free carriers to be enriched on the catalyst surface to participate in the piezocatalytic reactions. 47–49 Moreover, as revealed by the XPS results, the potential internal electric field is also beneficial for the transfer of electrons and holes mentioned above. As a result, the piezocatalytic performance of the CdS@SnS 2 heterojunction is markedly superior to that of single components.…”
Section: Resultsmentioning
confidence: 94%
“…In this case, the piezoelectric field will make electrons and holes transfer in opposite directions, thereby effectively inhibiting their recombination and allowing more free carriers to be enriched on the catalyst surface to participate in the piezocatalytic reactions. 47–49 Moreover, as revealed by the XPS results, the potential internal electric field is also beneficial for the transfer of electrons and holes mentioned above. As a result, the piezocatalytic performance of the CdS@SnS 2 heterojunction is markedly superior to that of single components.…”
Section: Resultsmentioning
confidence: 94%
“…7a. 44 Compared with PM-1 and PM-2, PM-3 holds the largest effective piezoelectric coefficient (9.05 pm V −1 ), which means it exhibits the strongest piezoelectric polarization. It has been confirmed that the catalyst with a higher piezoelectric response could induce a stronger piezoelectric field, thus immensely promoting piezocatalytic activity under an external mechanical force.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, it is hard to scientifically compare these works. The detailed parameters of each work referenced are listed in Table S2. ,,,, It can be seen that the yield rate of our BTNO is among the highest, showing its advantage for hydrogen peroxide production with only pure water by harvesting vibration energy. Furthermore, it is worth noting that the yield rate of 407.05 μmol·g –1 ·h –1 shown in Figure g was obtained under an ultrasound power of only 50 W, and this is much lower than the reported works wherein the ultrasonic power used is normally in the range of 120–300 W. As discussed in Figure e, the piezocatalytic performance will be enhanced along with increasing the ultrasonic power.…”
Section: Resultsmentioning
confidence: 99%
“…14 A range of piezocatalysts have been utilized to synthesize H 2 O 2 , including g-C 3 N 4 , 9 metal oxides such as BaCaZrTi perovskite oxide, 4 BaTiO 3 , 15 (Bi 0.5 Na 0.5 )-TiO 3 , 16 and NaNbO 3 . 17 Bismuth layered compounds, which are composed of [Bi 2 O 2 ] 2+ slices and interleaved anions and/or anionic groups, have also demonstrated their applications in H 2 O 2 preparation under the mechanical vibration such as Bi 4 Ti 3 O 12 , 18,19 BiOCl, 20 Bi 4 O 5 Br 2 , 21 etc. The application of bismuth layered compounds as piezo-catalysts is related to their noncentrosymmetric characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation